Shikwa and Jawab-i-Shikwa : Iqbal's Dialogue with Allah - Iqbal, Muhammad, Sir; Translated and introducted by Khushwant Singh; Foreword by Rafiq Zakaria (New Delhi Oxford University Press, 1990)
Two of the best-known works from an Indian poet are presented in this volume, translated from the Urdu. They extol the legacy of Islam and its civilizing role in history, and confront the dilemma of Islam in modern times.
Though much of Iqbal's best poetry is written in Persian, he is also a poet of colossal stature in Urdu. Shikwa (1909) and Jawab-i-Shikwa (1913) extol the legacy of Islam and its civilising role in history, bemoan the fate of Muslims everywhere, and squarely confront the dilemmas of Islam in modern times. Shikwa is thus, in the form of a complaint to Allah for having let down the Muslims and Jawab-i-Shikwa is Allah's reply to the poet's complaint.
Shikwa and Jawab-e-Shikwa = Complaint and Answer : Iqbal's Dialogue with Allah.
Keywords: Urdu literature -- Urdu poetry -- Islam